1991
DOI: 10.1089/dna.1991.10.525
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer, Repressor, and Promoter Specificities Combine to Regulate the Rat α-Fetoprotein Gene

Abstract: The upstream transcription control region of the rat alpha-fetoprotein (AFP) gene was analyzed using transient expression of CAT genes in HepG2 cells which express the gene; H4C3 cells which repress the AFP gene but express the albumin gene; and four nonexpressing cell lines. Deletion analysis based on the DNA sequence resolved three upstream enhancers corresponding to the mouse AFP enhancers, but showed additional weak effects from flanking sequences. Quantitative experiments demonstrated that the three enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 22 publications
1
50
0
Order By: Relevance
“…This local enhancer makes a considerable contribution to albumin gene expression, equivalent to ϳ40% of the SV40 early enhancer plasmid SV2CAT, and the distant enhancers increase this activity to ϳ240% of SV2CAT. This amounts to 6-fold stimulation, but we have previously shown that in strong enhancer-driven systems, the enhancer contribution is described better as an additive relationship (10). In this paper, comparable enhancer activity stimulated the intact albumin promoter 2.4-fold, Ϫ84 promoter 32-fold, the ⌬4A promoter 48-fold (Fig.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…This local enhancer makes a considerable contribution to albumin gene expression, equivalent to ϳ40% of the SV40 early enhancer plasmid SV2CAT, and the distant enhancers increase this activity to ϳ240% of SV2CAT. This amounts to 6-fold stimulation, but we have previously shown that in strong enhancer-driven systems, the enhancer contribution is described better as an additive relationship (10). In this paper, comparable enhancer activity stimulated the intact albumin promoter 2.4-fold, Ϫ84 promoter 32-fold, the ⌬4A promoter 48-fold (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…Albumin Gene Promoter Models-Previous studies have demonstrated that the AFP gene enhancers are strongly active when combined with the albumin gene promoter (10,11,22). Our studies established enhancer stimulation of the promoter from distances of 1.7 kbp or greater, using a rat albumin promoter segment extending from ϩ1 to Ϫ308 bp (22).…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations